2021
DOI: 10.1158/2159-8290.cd-20-1201
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Vandetanib plus Everolimus for the Treatment ofACVR1-Mutant Diffuse Intrinsic Pontine Glioma

Abstract: Somatic mutations in ACVR1 are found in a quarter of children with diffuse intrinsic pontine glioma (DIPG), however there are no ACVR1 inhibitors licensed for the disease. Using an Artificial Intelligence-based platform to search for approved compounds for ACVR1-mutant DIPG, the combination of vandetanib and everolimus was identified as a possible therapeutic approach. Vandetanib, an inhibitor of VEGFR/RET/EGFR, was found to target ACVR1 (Kd=150nM) and reduce DIPG cell viability in vitro, but has limited abili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
(58 reference statements)
0
21
0
1
Order By: Relevance
“…On the therapeutic side, one direction for RTK-altered pediatric gliomas is co-treatment of multiple TKIs, or one TKI with a synergistic drug to avoid or delay the development of drug resistance ( 100 ). As discussed, our group showed that the combination of PDGFRA inhibitor dasatinib with mTOR inhibitor everolimus significantly improved the survival of pediatric high-grade glioma than either treatment alone ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the therapeutic side, one direction for RTK-altered pediatric gliomas is co-treatment of multiple TKIs, or one TKI with a synergistic drug to avoid or delay the development of drug resistance ( 100 ). As discussed, our group showed that the combination of PDGFRA inhibitor dasatinib with mTOR inhibitor everolimus significantly improved the survival of pediatric high-grade glioma than either treatment alone ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vandetanib was later investigated in combination with dasatinib in another phase I trial, with median OS of 15 months ( 99 ). In addition, vandetanib and everolimus showed promising preclinical results and initial clinical case studies ( 100 ). Pazopanib targets several TKIs (among them VEGFR, KIT, PDGFR, and FGFR) to inhibit tumor angiogenesis; it was investigated in a phase II adult glioblastoma trial and did not prolong survival ( 101 ).…”
Section: Promising Therapiesmentioning
confidence: 99%
“…The development of new treatments and drug repurposing is also an important issue ( 48 ). Interesting studies with initial evidence in this respect have recently been published ( 49 ). More tolerable and safe treatments would significantly improve the quality of life in this population.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the blood supply to the tumor and tumor volume, the patient took 2.6 mg/m 2 /day rapamycin orally (divided into two equal doses) at the initial recommended dose of complicated vascular anomalies, but the trough concentration of plasma rapamycin was under 10–15 ng/ml after 7 days of rapamycin treatment. According to some reports, the recommended dose for children with brain tumors is 3–5 mg/m 2 /day ( 25 27 ), and the maximum dose for recurrent and refractory solid tumors reaches 150 mg/m 2 /day (once a week) without serious rapamycin-induced adverse effects ( 28 ). Furthermore, because of low oral bioavailability (15%–20%) ( 29 ) and poor blood–brain barrier penetration ( 30 32 ) [the ratio of the cerebrospinal fluid rapamycin concentration to the plasma rapamycin concentration was 0.0057 ( 33 )], the patient with aCPP finally received 7.8 mg/m 2 /day (divided into two equal doses), and the trough concentration of plasma rapamycin reached 14.8 ng/ml.…”
Section: Discussionmentioning
confidence: 99%